Analysis of the Lack of Interest of MSMEs in Fintech In Medan Denai - Putri Indah Fadillah; Muhammad Irwan Padli Nasution; Muhammad Ikhsan Harahap (UNIVED Press, 2024)
The government will address the issue of population explosion, which will be very important for economic development especially in Medan City, the government also encourages the growth and empowerment of MSMEs. Therefore, government-owned small and medium enterprises must be developed to be empowered. People may be motivated to move forward in their business with MSMEs in Medan Denai. Until 2021, the number of fintech companies is expected to continue to grow due to a number of variables, including convenience, excellence, service features, risk, and trust. the convenience of using fintech is easy to understand and does not require a lot of work, but umkm in Medan Denai still do not understand the use of fintech. therefore the purpose of this research is to analyze the Lack of Interest of MSMEs in Fintech in Medan Denai. This research uses a qualitative approach that is descriptive and explains the study in the field. The analysis method used is an analysis of the results of interviews and field observations conducted by researchers. In addition, the study techniques include using primary data from interviews with 10 MSME players in Medan Denai in July to those who have or have not used fintech in their operations. These 10 MSMEs are MSMEs that are a requirement for this research. According to the findings of the study, 1. Intention to use fintech services is concluded that the majority of traders are aware of the existence of fintech. Personalization is concluded that for those who know fintech, they consider fintech easy to use, but there are some MSME players who do not know fintech so they cannot make conclusions. 3. The ability to access fintech, almost all of them answered that fintech can be used anywhere, because fintech is on a cellphone that can be taken anywhere. The features that exist in fintech for them are difficult and some are not, depending on their use. 4. Technological innovativeness, namely some informants said that fintech has been able to provide services according to existing needs but some have not, it is because some of these fintechs do not have fintech guides making them feel helped in terms of buying and selling services 5. Social factors, namely for those who use fintech, they say that they use it because of the invitation of friends and people around, but there are also those who already know from the beginning. All informants said that fintech makes a business competitive and is able to make its business superior, it happens because nowadays many people make payments through fintech.